Penggelapan terhadap Uang Titipan oleh Notaris dalam Pembuatan Perjanjian Kerjasama - ., Melyana (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 01 (2022), 2022)
This article aims to examine the responsibility of the Notary who embezzled money deposited by the appearer in the District Court Decision No. 29/PID.B/2020/PN PWK. In this article, author uses normative research method. The Notary who receives the deposited money has violated Article 52 Paragraph (1) of the UUJN, because the Notary is indirectly a party to the deposit agreement. This resulted in based on Article 52 Paragraph (3) UUJN, the authentic deed was degraded its evidentiary strength into an underhand deed and the Notary could be sued to reimburse fees, interest and losses. In addition, Court Decision No. 29/PID.B/2020/PN.Pwk made a mistake in passing the verdict, where the Notary should have been punished based on Article 374 of the Criminal Code regarding embezzlement by weighting. Given that, the Notary has received the money because he holds the position of a Notary who is highly trusted and is considered a neutral party by the appearers. Besides, based on Article 13 jo. Article 374 KUHP, the Notary who commits embezzlement can be given office sanctions ranging from a written warning to dishonorable discharge.